Protection of 6-35 kV overhead power lines against direct lightning strikes - Danylchenko, D. O.; Dryvetskyi, S. I.; Shevchenko, S. Yu. (Serednyak T. K., 2023)
The monograph is devoted to the solution of an actual scientific and applied problem in the field of lightning protection of overhead power lines with protected wires of medium voltage classes from direct lightning strikes. The paper experimentally proved that protected wires are less likely to be affected by direct lightning strikes than non-insulated wires. This is due to the protective sheath of the protected wires, since the conditions for the occurrence of an oncoming conductor become much more complicated, and the area of lightning capture is significantly reduced. Current methods of calculating the number of direct lightning strikes do not take into account the type of wire on overhead lines, which leads to incorrect calculations of the number of direct lightning strikes and, as a result, the number of line shutdowns. The obtained results made it possible to create a new approach to lightning protection of overhead lines with protected wires, to create a combined power transmission line. This line contains in its design protected wires and a non-insulated wire, which performs the role of a lightning protection wire. The created model of the combined line was tested experimentally, not a single lightning strike to the protected wires was recorded.
Keywords: monograph; electrical transmission lines; lightning surges; pulses; voltage; mathematical model